Chronic, Recreational Chloroform-Induced Liver Injury - Emily A. Minor; Mackenzie S. Newman; Justin T. Kupec (Case Reports in Hepatology)
Historically used as an anesthetic, chloroform is a halogenated hydrocarbon that is associated with central nervous system depression, arrhythmias, and hepatotoxicity. It is no longer used clinically, but accidental and intentional poisonings still occur. We report a case of chronic chloroform abuse leading to severe hepatotoxicity in a 26-year-old male graduate student. The patient presented to the emergency department with a three-day history of abdominal pain, dehydration, and scleral icterus. He drank several beers the night before the onset of symptoms, but denied taking acetaminophen, ibuprofen, or other drugs. An extensive work-up revealed an aspartate aminotransferase (AST) of 13,527 U/L and alanine aminotransferase (ALT) of 8,745 U/L, but the cause of his liver injury could not be determined. It was not until many months later that the patient admitted to inhaling chloroform in the weeks leading up to his illness.